Transformative Learning and Professional Identity Formation During International Health Electives: A Qualitative Study Using Grounded Theory. (September 2018) - Sawatsky, Adam P.; Nordhues, Hannah C.; Merry, Stephen P.; Bashir, M. Usmaan; Hafferty, Frederic W.
Abstract : Purpose: International health electives (IHEs) are widely available during residency and provide unique experiences for trainees. Theoretical models of professional identity formation and transformative learning may provide insight into residents' experiences during IHEs. The purpose of this study was to explore transformative learning and professional identity formation during resident IHEs and characterize the relationship between transformative learning and professional identity formation. Method: The authors used a constructivist grounded theory approach, with the sensitizing concepts of transformative learning and professional identity formation to analyze narrative reflective reports of residents' IHEs. The Mayo International Health Program supports residents from all specialties across three Mayo Clinic sites. In 2015, the authors collected narrative reflective reports from 377 IHE participants dating from 2001 to 2014. Reflections were coded and themes were organized into a model for transformative learning during IHEs, focusing on professional identity. Results: Five components of transformative learning were identified during IHEs: a disorienting experience; an emotional response; critical reflection; perspective change; and a commitment to future action. Within the component of critical reflection, three domains relating to professional identity were identified: making a difference; the doctor–patient relationship; and medicine in its "purest form." Transformation was demonstrated through perspective change and a commitment to future action, including continued service, education, and development. Conclusions: IHEs provide rich experiences for transformative learning and professional identity formation. Understanding the components of transformative learning may provide insight into the interaction between learner, experiences, and the influence of mentors in the process of professional identity formation.